Pulmonary Artery Cement Embolism after a Vertebroplasty - Anas Nooh; Fahad H. Abduljabbar; Ahmed H. Abduljabbar; Peter Jarzem (Case Reports in Orthopedics)
Background Context. Vertebroplasty is a minimally invasive procedure most commonly used for the treatment of vertebral compression fractures. Although it is relatively safe, complications have been reported over time. Among those complications, massive cement pulmonary embolism is considered a rare complication. Here we report a case of massive diffuse cement pulmonary embolism following percutaneous vertebroplasty for a vertebral compression fracture. Study Design. Case report. Methods. This is a 70-year-old female who underwent vertebroplasty for T11 and T12 vertebral compression fracture. Results. CT-scan revealed an incidental finding of cement embolism in the pulmonary trunk and both pulmonary arteries. Since the patient was asymptomatic, she was monitored closely and she did not need any intervention. Conclusion. Vertebroplasty is a minimally invasive procedure used for treatment of vertebral compression fracture. Despite the low rate of complications, a pulmonary cement embolism can occur. The consequences of cement embolism range widely from being asymptomatic to embolism that can cause paralysis, radiculopathy, or a fatal pulmonary embolism.